METAPHOR AND ITS TYPES IN MODERN FRENCH (Scientific journal of the Fergana State University, 2026)
The polysemy of words enables a single word to express multiple concepts. Metaphors arise as a result of a word partially departing from its original meaning and acquiring additional semantic layers. As one of the most productive linguistic phenomena, metaphor allows for the understanding of relationships between objects and events. In French, metaphor is a figure of speech based on analogy, involving the use of words in a figurative sense to denote an object or event on the basis of similarity. In modern French, metaphor plays a significant role both in enriching the lexical stock of the language and in creating expressive imagery. As a product of human cognition, metaphor is employed not only in literary discourse but also in scientific and journalistic styles. Metaphors in the French language are generally classified into two main types: living metaphors and lexicalized metaphors. Nouns, adjectives, verbs, and adverbs are the principal parts of speech most prone to metaphorization. This article examines metaphor in contemporary French, focusing on its types as well as its lexical, grammatical, and stylistic features. The analysis is supported by examples drawn from works of fiction.